Platelet and Plasma Phosphatidylcholines as Biomarkers to Diagnose Cerebral Amyloid Angiopathy - Foidl, Bettina M.; Oberacher, Herbert; Marksteiner, Josef; Humpel, Christian (Frontiers in Neurology, 2020)
Alzheimer’s disease (AD) is a severe neurodegenerative brain disorder and characterized by deposition of extracellular toxic beta-amyloid(42) plaques and the formation of intracellular tau neurofibrillary tangles. In addition, beta-amyloid peptide deposits are found in the walls of small to medium blood vessels termed cerebral amyloid angiopathy (CAA). However, the pathogenesis of CAA appears to differ from that of senile plaques in several aspects. The aim of the present study was to analyze different lipids (phosphatidylcholines (PCs) and lysoPCs) in platelets and plasma of a novel mouse model of sporadic CAA (Foidl and Humpel, 2019). Our data show that lipids are significantly altered in plasma of the CAA mice. Levels of 8 diacyl PCs, 2 acyl-alkyl PCs and 2 lysoPCs were significantly increased. In extracts of mouse blood platelets 4 diacyl and 2 acyl-alkyl PCs (but not lysoPCs) were significantly altered. Our data show that lipids are changed in CAA with a specific pattern and we provide for the first time evidence that selected platelet and plasma phosphatidylcholines may help to characterize CAA.